Comparison of the levonorgestrel‐releasing intrauterine system, hysterectomy, and endometrial ablation for heavy menstrual bleeding in a decision analysis model1. Issue 2 (1st September 2017) - Louie, Michelle; Spencer, Jennifer; Wheeler, Stephanie; Ellis, Victoria; Toubia, Tarek; Schiff, Lauren D.; Siedhoff, Matthew T.; Moulder, Janelle K.
Abstract: Background: A better understanding of the relative risks and benefits of common treatment options for abnormal uterine bleeding (AUB) can help providers and patients to make balanced, evidence‐based decisions. Objectives: To provide comparative estimates of clinical outcomes after placement of levonorgestrel‐releasing intrauterine system (LNG‐IUS), ablation, or hysterectomy for AUB. Search strategy: A PubMED search was done using combinations of search terms related to abnormal uterine bleeding, LNG‐IUS, hysterectomy, endometrial ablation, cost‐benefit analysis, cost‐effectiveness, and quality‐adjusted life years. Selection criteria: Full articles published in 2006–2016 available in English comparing at least two treatment modalities of interest among women of reproductive age with AUB were included. Data collection and analysis: A decision tree was generated to compare clinical outcomes in a hypothetical cohort of 100 000 premenopausal women with nonmalignant AUB. We evaluated complications, mortality, and treatment outcomes over a 5‐year period, calculated cumulative quality‐adjusted life years (QALYs), and conducted probabilistic sensitivity analysis. Main results: Levonorgestrel‐releasing intrauterine system had the highest number of QALYs (406 920), followed by hysterectomy (403 466), non‐resectoscopic ablation (399 244), and resectoscopic ablation (395 827). Ablation had more treatment failures and complications than LNG‐IUS and hysterectomy. Findings were robust in probabilistic sensitivity analysis. Conclusions: Levonorgestrel‐releasing intrauterine system and hysterectomy outperformed endometrial ablation for treatment of AUB. Abstract : The levonorgestrel‐releasing intrauterine system and hysterectomy are associated with a higher quality of life and fewer complications than endometrial ablation for abnormal uterine bleeding.